Open source multi-platform NooJ for NLP - Silberztein, Max; Váradi, Tamás; Tadić, Marko (2012)
The purpose of this demo is to introduce the linguistic development tool NooJ. The tool has been in development for a number of years and it has a solid community of computational linguists developing grammars in two dozen languages ranging from Arabic to Vietnamese . Despite its manifest capabilities and reputation, its appeal within the wider HLT community was limited by the fact that it was confined to the .NET framework and it was not open source. However, under the auspices of the CESAR project it has recently been turned open source and a JAVA and a MONO version have been produced. In our view this significant development justifies a concise but thorough description of the system, demonstrating its potential for deployment in a wide variety of settings and purposes. The paper describes the history, the architecture, main functionalities and potential of the system for teaching, research and application development.
Projekt MZOS
ENG